CUSTOMER SATISFACTION AND TRUST – ARE THEY RELATED WITH BUYING FREQUENCY AND THE LENGTH OF THE RELATION? - Stoian (Bobalca) Claudia; Danilet Magdalena (Annals of the University of Oradea: Economic Science, 2017)
The purpose of this research is to investigate the connection between the buying behavior and the level of customer trust and general satisfaction. The buying behavior was measured by two variables: the length of the relation between the customer and the company and the buying frequency. In order to measure trust, we explored two dimensions of this construct: trust in the salesperson and trust in the company brand. Research objectives: (1) To identify the connection between the length of the customer - company relation and clients’ general satisfaction; (2) To identify the connection between the length of the customer - company relation and trust; (3) To identify the connection between buying frequency and clients’ general satisfaction; (4) To identify the connection between buying frequency and trust. We conducted a quantitative survey on a sample of 807 young buyers of cosmetic products. The respondents were only female students, 19-25 years who brought cosmetic products from direct selling companies. We created two groups of buyers, using as a variable the length of the relation between the clients and the company: first group includes the clients who buy from the company from less than 2 years; the second group includes the clients who buy from the company from more than 2 years. We also created two groups of buyers, using as a variable the frequency of buying cosmetic products from direct selling companies: first group is represented by the clients buy from the company every month or once every 2 months; the second group is represented by the clients buy from the company once every 3 months or less. The questionnaire was build based on a previous exploratory research. The results of the present study indicated that the clients who buy from the company from less than 2 years are more satisfied of the company and have more trust in the brand than the old clients.